Comparison between Accelerated Solvent Extraction (ASE) with clean up in-line and Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) extraction in honey. (International Journal of Health, Animal Science and Food Safety, 2016)
of contaminants and safe for the consumers. Many pollutants, including pesticides (Chauzat et al,2011) and heavy metals (Tuzen et al., 2007) coming from the environment, could be the source ofcontamination for bee matrices. In this study the method performances of two solid- liquidextraction techniques, Accelerated Solvent Extraction (ASE) with clean up in-line and Quick, Easy,Cheap, Effective, Rugged, and Safe (QuEChERS) extraction, were evaluated and compared for theanalysis of pesticide residues in honey. Fiftythree pesticides, belonging to different chemicalclasses, were investigated in orange blossom honey from German local market using method basedon Gas Chromatography coupled with Tandem Mass Spectrometry (GC-MS/MS. The linearity (R2 >0.985) in solvent and in matrix was achieved for most of the compounds with both extractiontechniques, however showing a strong matrix effect. The criteria for a good repeatability (CV
Keywords: Pesticide residues; analytical chemistry; mass spectrometry; honey.